Library Disaster Preparedness in Southeast Asia: A Systematic Review - Abidin, Azraai; Abdullah, Mohd Najib; Shaari, Noor Faezah; Saad, Nur Shurbaniah (UI Scholars Hub, 2024)
This systematic review, which follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, examines the current state of disaster preparedness in libraries across Southeast Asia. It evaluates existing research using four core emergency preparedness rule elements: risk assessment and planning, the communication plan, policies and procedures, and training and testing. While an initial search identified 488 potential studies, only seven met the strict criteria; these seven studies were from Indonesia, Malaysia, and the Philippines. This indicates either a significant gap in library readiness or a lack of comprehensive research on the subject. The results show that most libraries, including those that have previously experienced disasters, lack disaster preparedness. Hence, it is essential to make a collective effort to bridge this research gap by creating research opportunities that focus on developing disaster preparedness programs for each country within the region. By utilizing the best practices and knowledge produced by future studies, libraries in Southeast Asia can enhance their resilience and preparedness to effectively reduce the impact of disasters. Ultimately, this will safeguard their valuable resources and enable them to continue providing the best service to their communities.